Identification and genetic diversity analysis of a male-sterile gene (MS1) in Japanese cedar (Cryptomeria japonica D. Don) - Yoichi Hasegawa (Nature Portfolio, 2021)
Abstract Identifying causative genes for a target trait in conifer reproduction is challenging for species lacking whole-genome sequences. In this study, we searched for the male-sterility gene (MS1) in Cryptomeria japonica, aiming to promote marker-assisted selection (MAS) of male-sterile C. japonica to reduce the pollinosis caused by pollen dispersal from artificial C. japonica forests in Japan. We searched for mRNA sequences expressed in male strobili and found the gene CJt020762, coding for a lipid transfer protein containing a 4-bp deletion specific to male-sterile individuals. We also found a 30-bp deletion by sequencing the entire gene of another individual with the ms1. All nine breeding materials with the allele ms1 had either a 4-bp or 30-bp deletion in gene CJt020762, both of which are expected to result in faulty gene transcription and function. Furthermore, the 30-bp deletion was detected from three of five individuals in the Ishinomaki natural forest. From our findings, CJt020762 was considered to be the causative gene of MS1. Thus, by performing MAS using two deletion mutations as a DNA marker, it will be possible to find novel breeding materials of C. japonica with the allele ms1 adapted to the unique environment of each region of the Japanese archipelago.